Prediction of Layer Chicken Disease using Fuzzy Analytical Hierarcy Process - Muslihudin, Muhammad; Wanti, Risma; ., Hardono; ., Nurfaizal; K, Shankar; M, Ilayaraja; Maseleno, Andino; ., Fauzi; Rohmadi Mustofa, Dwi; Masrur, Muhammad; Mukodimah, Siti (International Journal of Engineering and Technology, 2018)
Chicken disease belong to the herpes group that often attacks poultry like laying hens. Various types of diseases that can attack such as marek, IB chicken, chicken NP, CA, EDS. Therefore it is necessary to be given a special vaccine for poultry that can anticipate the dominant diseases attacking poultry in particular chicken laying. So need a prediction model with the concept of fuzzy analytical hierarchy process. analytical hierarchy process is one of the methods in the decision-making system that uses several variables with a multilevel analysis process using criteria such as decreased egg production, cough, watery eyes, wings hanging down, a gray sprocket, legs paralyzed. From the test results obtained varied values with alternative results obtained: Marek 0.1487, IB chicken 0.3464, CA 0.1769, chicken NP 0.2407, EDS 0.0884. Then fuzzy analytical hierarcy process is good for predicting laying hens disease